الصراع الفلسطيني الصهيوني الراهن ومستقبل القضية الفلسطينية بعد طوفان الأقصى - قريب نورة (جامعة المسيلة, 2025)
This study outlines the development of the Palestinian-Zionist conflict from the late 19th century to the 2023 “Al-Aqsa Flood” operation. It highlights the rise of Zionism at the 1897 Basel Conference, driven by European anti-Semitism and colonial ambitions, with British support solidified through the Balfour Declaration. This led to increased Jewish immigration and the 1948 Nakba, which displaced hundreds of thousands of Palestinians. Key moments included the 1967 and 1973 wars and the two Intifadas, which shifted the struggle toward organized resistance. The “Al-Aqsa Flood” operation in 2023 marked a major turning point by exposing Israeli vulnerabilities and rejecting failed peace efforts. It aimed to defend Palestinian rights and restore the issue to international focus. Israel's military response caused heavy destruction but failed to achieve clear goals. The conflict is ultimately framed as a struggle between settler-colonialism and a national liberation movement.